2017
DOI: 10.1002/cpmo.22
|View full text |Cite
|
Sign up to set email alerts
|

Cre‐loxP‐Mediated Recombination: General Principles and Experimental Considerations

Abstract: The cre-loxP-mediated recombination system (the "cre-loxP system") is an integral experimental tool for mammalian genetics and cell biology. Use of the system has greatly expanded our ability to precisely interrogate gene function in the mouse, providing both spatial and temporal control of gene expression. This has been largely due to the simplicity of its use and its adaptability to address diverse biological questions. While the use of the cre-loxP system is becoming increasingly widespread, in particular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 78 publications
0
90
0
1
Order By: Relevance
“…Arguably one of the most important technological advancements in the study of gene function has been the development of gene "knock‐outs" and "knock‐ins." Furthermore, the conditional targeting by cell or tissue specific promoters using the Cre/loxP system has been instrumental in elucidating gene function in specific cell populations in vivo (reviewed in [1]). Further sophistication to this system was added by allowing temporal control by fusing the Cre recombinase to a mutated ligand binding domain of the estrogen receptor.…”
Section: Figurementioning
confidence: 99%
“…Arguably one of the most important technological advancements in the study of gene function has been the development of gene "knock‐outs" and "knock‐ins." Furthermore, the conditional targeting by cell or tissue specific promoters using the Cre/loxP system has been instrumental in elucidating gene function in specific cell populations in vivo (reviewed in [1]). Further sophistication to this system was added by allowing temporal control by fusing the Cre recombinase to a mutated ligand binding domain of the estrogen receptor.…”
Section: Figurementioning
confidence: 99%
“…While the allele is capable of recombination, we observed variable efficiency that appeared to be dependent on the cell type. While this could simply reflect variable expression or activity of individual Cre transgenes or recombinase, respectively (Bao, Ma, Schuster, Lin, & Yan, ; McLellan, Rosenthal, & Pinto, ), we hypothesize that a cis effect at the Irf6 locus contributes to the variable efficiency. This hypothesis is based on the following: (1) In this study, we observed no or incomplete recombination with the EIIa‐Cre “deleter strain,” and with two other tissue specific Cre transgenes, including K14‐Cre‐ER (Vasioukhin, Degenstein, Wise, & Fuchs, ) and Tgfb3‐Cre (Yang, Li, & Kaartinen, ; data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…The CreERT2 system, in combination with floxed genes allows visualization of cells, overexpression or suppression of their genes, cell ablation, inhibition, and excitation [36,37]. By combining mural cell promoter lines with fluorescent reporter lines, we enabled the visualization of individual mural cells for detailed morphological characterization.…”
Section: Mural Cell-specific Creert2 Lines For Basic Researchmentioning
confidence: 99%